PENERAPAN MODEL PEMBELAJARAN SNOWBALL-THROWING UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN EKONOMI KONSEP BANK DAN INDUSTRI KEUANGAN NON-BANK: (Studi kuasi eksperimen pada Peserta Didik Kelas X SMAN 1 Pagelaran Tahun Ajaran 2022/2023) - Alwiyasa, Rahmatul Khalik; Gumilar, Rendra; Srigustini, Astri (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
This study aims to determine the effect of the Snowball Throwing learning model to improve learning outcomes in economics subjects Concepts of Banks and the Non-Bank Financial Industry. The research method used is a quasi- experimental method in the form of a noun equivalent control group design. The population in this study were all class X students of SMAN 1 Pagelaran, totaling 152 students. The sampling technique was purposive sampling, that is, class X-3 (experimental class) with a total of 30 students and class X-5 (control class) with a total of 30 students. The data collection technique in this study was using multiple choice tests and the data analysis technique used was paired samples T-test and independent samples T-test. The results of this study indicate that 1) There are differences in the learning outcomes of students in the experimental class using the Snowball Throwing model in the initial and final measurements with an average n-gain value of 0.717 (high). 2) There are differences in the learning outcomes of students in the control class using conventional models in the initial measurement and final measurement with an average n-gain value of 0.697 (moderate). 3) There is no difference in increasing the ability of students' learning outcomes between the experimental class and the control class.